(untitled) (American Journal of Islam and Society, 2000)
Contemporary Islamic scholarship emerged in the mid-nineteenth century in response to the overall stagnation of Muslim society and culture. Muslim reformers advanced a simple but powerful thesis: overcoming the weaknesses and deficiencies of contemporary Muslim society requires profound social and cultural reforms, and hence a critical examination of traditional thought and institutions. The pioneers of contemporary Islamic reform were versed in both modem Western and traditional Islamic thought. Early reformers, such as Al- Afghani, Abduh, al-Kawakibi, and Iqbal critically engaged both the system of ideas inherited from the Muslim past and those received from the modern West. Their free spirit, inquisitive minds, and unyielding courage allowed them to place intellectual reform on a critical yet balanced path. While the tradition of critical thinking they espoused continues to grow and flourish among many contemporary Muslim thinkers, the balance they maintained in criticizing the self and the other has been lost by a large segment of Muslim intellectuals. Most Muslim intellectuals are critical of either traditional Muslim scholarship or Western thought, but seldom both. This one-sidedness has turned knowledge and scholarship into a partisan tool to be used against the perceived ideological adversary. Factors contributing to the one-sidedness of many contemporary Muslim scholars are numerous, and are often rooted in pure political or economic motives. Two factors, however, stand out as expressively theoretical and intellectual: the ahistorical view of ideas and concepts among Muslims, whereby what has been devised by early scholars is given universal and absolute validity; and the absence of an Archimedean point from which the intellectual can judge both. For over a century now, Muslim intellectuals have been divided into two major blocs, the advocates of modernity and the defenders of Islamic tradition. The former continue to see Islam as a premodern legacy, incapable of leading Muslim society into a challenging future. Trapped in an end-of-history mindset, they have not been able to develop a critical approach to ...